Korelasi antara Koordinasi Mata Tangan dan Kekuatan Otot Lengan dengan Medium Shoot pada Ekstrakulikuler Bola Basket MTSN 16 Jakarta - Iskandar, Muhammad; Sulaiman, Iman; Apriyanto, Tirto (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2024)
The purpose of this study was to determine (1) the relationship between hand eye coordination (X1) with medium shoot (Y), (2) the relationship between arm muscle strength (X2) and medium shoot (Y), (3) hand eye coordination relationship (X1), arm muscle strength (X2) together with medium shoot (Y). This research is a correlational quantitative research. The population of this study was basketball extracurricular students of MTSN 16 Jakarta. This research sample collection technique is purposive sampling a total of 10 people. The research instruments used were (1) hand eye coordination using the Wall bounce test instrument, (2) arm muscle strength using push-ups, (3) shooting test with medium shoot.. The hypothesis testing technique carried out in this study uses simple correlation statistical analysis techniques followed by t-tests at a significant level. The results of the first test showed a significant relationship between hand eye coordination (X1) with medium shoot (Y) with linear line equation Ŷ = 13.452 + 0.797 X1, correlation coefficient ry1 = 0.860 and determination coefficient (ry1²) = 0.739 which means that the variable of hand eye coordination contributes to medium shootby 73.9%. Secondly, there is a significant relationship between arm muscle strength (X2) and medium shoot (Y) with the linear line equation Ŷ = 46.362 + 0.942X2 correlation coefficient ry₂ = 0.873 and determination coefficient (ry₂²) = 0.762 which means that the variable arm muscle strength contributes to medium shoot 76.2%.Third, there is a significant relationship between hand eye coordination (X1), arm muscle strength (X2), together with medium shoot (Y) with the linear line equation Ŷ = = 44.592 + -0.027X1 + 1.121X2. correlation coefficient ry₁-₂ = 0.900 and determination coefficient (Ry₁.₂)² = 0.81 which means that the variables of hand eye coordination and arm muscle strength contribute to medium shoot by 81%.